From peer-based to peer-led: redefining the role of peers across the hepatitis C care pathway: HepCare Europe. (29th November 2019) - Surey, Julian; Menezes, Dee; Francis, Marie; Gibbons, John; Sultan, Binta; Miah, Ala; Abubakar, Ibrahim; Story, Alistair
Abstract: Background: HCV infection disproportionately affects underserved populations such as homeless individuals, people who inject drugs and prison populations. Peer advocacy can enable active engagement with healthcare services and increase the likelihood of favourable treatment outcomes. Objectives: This observational study aims to assess the burden of disease in these underserved populations and describe the role of peer support in linking these individuals to specialist treatment services. Methods: Services were identified if they had a high proportion of individuals with risk factors for HCV, such as injecting drug use or homelessness. Individuals were screened for HCV using point-of-care tests and a portable FibroScan. All positive cases received peer support for linkage to specialist care. Information was gathered on risk factors, demographics and follow-up information regarding linkage to care and treatment outcomes. Results: A total of 461 individuals were screened, of which 197 (42.7%) were chronically infected with HCV. Referral was made to secondary care for 176 (89.3%) and all received peer support, with 104 (52.8%) individuals engaged with treatment centres. Of these, 89 (85.6%) started treatment and 76 (85.4%) had a favourable outcome. Factors associated with not being approved for treatment were recent homelessness, younger age and current crack cocaine injecting. Conclusions: Highly trained peer support workers working as part of a specialist outreach clinical team help to identify a high proportion of individuals exposed to HCV, achieve high rates of engagement with treatment services and maintain high rates of treatment success amongst a population with complex needs.